A catalogue of Nolidae Bruand, 1846 from India (Lepidoptera, Noctuoidea) - Joshi, Rahul; Singh, Navneet; Kuni, Nikhil (Zootaxa, 2021)
The present catalogue is the first résumé of the family Nolidae Bruand, 1846 recorded in India comprising 354 species under 98 genera of 6 subfamilies, including four new records to India: Casminola seminigra (Hampson, 1896), Evonima ronkaygabori Han & Hu, 2019, Meganola suffusata (Wileman & West, 1929) and Nola euryzonata (Hampson, 1900). The Indian Nolidae represents 16.2 % of the global species (2,179 species) of Nolidae. The information on the type locality, type depository, sex of the type (wherever available), first reference, synonymy, host plants (wherever available) and distribution within as well as outside India for each of the included species is provided. Some clarifications regarding type locality, type depository along with new distributional records within Indian states are also given with 72 images of adults.